2019
DOI: 10.1002/phar.2211
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Statin Therapy on the Risk of Intracerebral Hemorrhage in Korean Patients with Hyperlipidemia

Abstract: Study ObjectiveStatins are widely used for primary and secondary prevention of cardiovascular and cerebrovascular disease. Several large randomized trials have suggested that statins might increase the risk of intracerebral hemorrhage (ICH); studies have also shown interethnic variability in responses to statins. This study aimed to determine the association between statin use and the risk of ICH in patients with hyperlipidemia among a Korean population.DesignPopulation‐based, retrospective cohort study.Data S… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
21
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 20 publications
(24 citation statements)
references
References 46 publications
0
21
1
Order By: Relevance
“…Therefore, these factors were not included. Second, only patients with hyperlipidemia were included in this study to analyze the effects of statin adherence because statins are used as first-line therapy to reduce LDL-C levels in such patients [9]. Therefore, further research including other CVDs is required.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Therefore, these factors were not included. Second, only patients with hyperlipidemia were included in this study to analyze the effects of statin adherence because statins are used as first-line therapy to reduce LDL-C levels in such patients [9]. Therefore, further research including other CVDs is required.…”
Section: Discussionmentioning
confidence: 99%
“…Evidence suggests that LDL-C levels are significant predictors of the risks associated with residual cardiovascular events [8]. Statins are used as first-line therapy to reduce LDL-C levels in patients with hyperlipidemia [9]. Over the past few decades, statins have also been used to treat dyslipidemia [10].…”
Section: Introductionmentioning
confidence: 99%
“…This risk seemed particularly enhanced in patients with prior intracerebral hemorrhage ( 52 ). However, subsequent sub-analysis of these trials and later studies including the TST trial (as discussed before) have not confirmed this association ( 16 19 , 21 , 53 – 56 ). For instance, a meta-analysis of 31 randomized clinical trials of statins did not find any increase in the risk of intracerebral hemorrhage among statin-treated patients, while reporting a reduction in all-cause mortality and all stroke types with statin therapy ( 53 ).…”
Section: Specific Scenariosmentioning
confidence: 94%
“…The same group reported that, in a population without prior history of stroke, those taking statins had lower intracerebral hemorrhage risk compared with those who did not receive statin therapy ( 55 ). Another large population-based study in Korean hyperlipidemic patients without history of haemorrhagic stroke, found that statin therapy was associated with a decreased risk of intracerebral hemorrhage and with improvements in ischemic cardiovascular and cerebrovascular outcomes ( 56 ). According to some observational studies, the potential link between statin use and intracerebral hemorrhage may be enhanced in patients with a background of cerebral angiopathies such as cerebral amyloid angiopathy or CADASIL (Cerebral Autosomal Dominant Arteriopathy with Sub-cortical Infarcts and Leukoencephalopathy) ( 57 ).…”
Section: Specific Scenariosmentioning
confidence: 99%
“…A pre-index of 365 days, our base-case, is quite common in previous studies on chronic medications. [29][30][31] In addition, we defined the basecase for the minimum period of medication use, which was referred to how long medications were taken, as 90 days and set the observation period of 3 years in the current study. 32…”
Section: Category (2): "Inclusion Criteria and Observation Period"mentioning
confidence: 99%